Environmental levels of Zn do not protect embryos from Cu toxicity in three species of amphibians. (July 2016) - Weir, Scott M.; Flynn, R. Wesley; Scott, David E.; Yu, Shuangying; Lance, Stacey L.
Abstract: Contaminants often occur as mixtures in the environment, but investigations into toxicity usually employ a single chemical. Metal contaminant mixtures from anthropogenic activities such as mining and coal combustion energy are widespread, yet relatively little research has been performed on effects of these mixtures on amphibians. Considering that amphibians tend to be highly sensitive to copper (Cu) and that metal contaminants often occur as mixtures in the environment, it is important to understand the interactive effects that may result from multiple metals. Interactive effects of Cu and zinc (Zn) on amphibians have been reported as antagonistic and, conversely, synergistic. The goal of our study was to investigate the role of Zn in Cu toxicity to amphibians throughout the embryonic developmental period. We also considered maternal effects and population differences by collecting multiple egg masses from contaminated and reference areas for use in four experiments across three species. We performed acute toxicity experiments with Cu concentrations that cause toxicity (10–200 μg/L) in the absence of other contaminants combined with sublethal concentrations of Zn (100 and 1000 μg/L). Our results suggest very few effects of Zn on Cu toxicity at these concentrations of Zn. As has been previously reported, we found that maternal effects and population history had significant influence on Cu toxicity. The explanation for a lack of interaction between Cu and Zn in this experiment is unknown but may be due to the use of sublethal Zn concentrations when previous experiments have used Zn concentrations associated with acute toxicity. Understanding the inconsistency of amphibian Cu/Zn mixture toxicity studies is an important research direction in order to create generalities that can be used to understand risk of contaminant mixtures in the environment. Graphical abstract: Highlights: We investigate the effect of Zn on acute Cu toxicity in three anuran species. Zn consistently had no significant effects on Cu toxicity at selected concentrations. The independent action model provides further evidence that Cu and Zn are additive. The interaction between Cu and Zn may be dependent on the concentrations tested. Abstract : For three species of amphibians, environmentally relevant Zn concentrations consistently had no significant effects on acute toxicity of Cu.